Smoothness of solutions with respect to multi-strip integral boundary conditions for nth order ordinary differential equations - Henderson, Johnny (Nonlinear Analysis: Modelling and Control, 2014)
Under certain conditions, solutions of the boundary value problem y(n) = f(x,y,y’,...,y(n-1)), a < x < b, y(i-1)(x1) = yi, i=1,...,n-1, y(x2) ∑ i=1mγi ∫ ξiηiy(x)dx=yn, a<x1<ξ1<η1<ξ2<η2<...<ξm<ηm<x2<b, are differentiated with respect to the boundary conditions.